2021
DOI: 10.4314/njb.v38i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom-mediated delignification of agricultural wastes for bio-ethanol production

Abstract: Biological pretreatment is a cost-effective method of delignifying lignocellulosic biomass, making it less recalcitrant to hydrolysis into fermentable sugars. In this study, selected agricultural wastes were pretreated with mushrooms (Lentinus squarrosulus and Pleurotus ostreatus) to delignify them for bioethanol production. The substrates were supplemented with 0.2 % CaCO3, inoculated with 12 % (w/w) L. squarrosulus and Pleurotus ostreatus spawns and incubated at 25 oC for 21 days. The highest lignin removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The pods were pretreated biologically using Ganoderma lucidum, Pleurotus eryngii, Pleurotus pulmonarius, and Hypsizygus ulmarius obtained from TLC mushrooms Limited, Nigeria. These fungi were chosen because research has shown that members of white rot fungi are the most efficient organisms for delignification as they produce different kinds of lignin-modifying enzymes such as laccase (Lac), manganese peroxidase (MnP), lignin peroxidase (LiP), and versatile peroxidase (VP) (Manavalan et al, 2015;Ahmed El-Imam et al, 2021). A total of six hundred grams (600 g) of the substrate were put into jute bags, which were then weighed after being moistened to a moisture content of 52 % (w/w) using sterile distilled water.…”
Section: Pap Collection and Biological Pretreatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The pods were pretreated biologically using Ganoderma lucidum, Pleurotus eryngii, Pleurotus pulmonarius, and Hypsizygus ulmarius obtained from TLC mushrooms Limited, Nigeria. These fungi were chosen because research has shown that members of white rot fungi are the most efficient organisms for delignification as they produce different kinds of lignin-modifying enzymes such as laccase (Lac), manganese peroxidase (MnP), lignin peroxidase (LiP), and versatile peroxidase (VP) (Manavalan et al, 2015;Ahmed El-Imam et al, 2021). A total of six hundred grams (600 g) of the substrate were put into jute bags, which were then weighed after being moistened to a moisture content of 52 % (w/w) using sterile distilled water.…”
Section: Pap Collection and Biological Pretreatmentmentioning
confidence: 99%
“…Its advantages include low cost, low severity (Taufikurahman et al, 2020), low energy and additive requirements, and the absence of fermentation inhibitors, toxic end-products, and effluents. Biological pretreatment frequently utilizes the white-rot fungi Trametes versicolor, Pleurotus sp., Phanerochaete chrysosporium, and Lentinus squarrosulus to delignify the biomass (Sindhu et al, 2016;Ahmed El-Imam et al, 2021). The residual carbohydrates are then readily depolymerized into sugars and fermented into bioethanol.…”
Section: Introductionmentioning
confidence: 99%
“…The pods were pretreated biologically using Ganoderma lucidum, Pleurotus eryngii, Pleurotus pulmonarius, and Hypsizygus ulmarius obtained from TLC mushrooms Limited, Nigeria. These fungi were chosen because research has shown that members of white rot fungi are the most efficient organisms for delignification as they produce different kinds of lignin-modifying enzymes such as laccase (Lac), manganese peroxidase (MnP), lignin peroxidase (LiP), and versatile peroxidase (VP) (Manavalan et al, 2015;Ahmed El-Imam et al, 2021). A total of six hundred grams (600 g) of the substrate were put into jute bags, which were then weighed after being moistened to a moisture content of 52 % (w/w) using sterile distilled water.…”
Section: Pap Collection and Biological Pretreatmentmentioning
confidence: 99%
“…Its advantages include low cost, low severity (Taufikurahman et al, 2020), low energy and additive requirements, and the absence of fermentation inhibitors, toxic end-products, and effluents. Biological pretreatment frequently utilizes the white-rot fungi Trametes versicolor, Pleurotus sp., Phanerochaete chrysosporium, and Lentinus squarrosulus to delignify the biomass (Sindhu et al, 2016;Ahmed El-Imam et al, 2021). The residual carbohydrates are then readily depolymerized into sugars and fermented into bioethanol.…”
Section: Introductionmentioning
confidence: 99%